Indeterminate results of QuantiFERON-TB Gold in-tube due to high nil concentration and methodological exploration and improvement - Peng, Wanchan; Wu, Siyu; Chen, Wei; Zhang, Yunli; Fu, Jinfang; Qiu, Ling; Wang, Wei (Clinica chimica acta, 2022)
•1. Indeterminate results of QuantiFERON-TB Gold in-Tube (QFT-GIT) can be due to failure of the positive control tube, or due to failure of the negative control tube. The first scenario is related to host immunosuppression, a topic that has been investigated in a number of recent studies. However, few studies to date have described the frequency and features of indeterminate results with high IFN-γ levels in negative control tubes (Nil > 8);•2. The study investigate the features of indeterminate results (ITRs) due to high concentrations of interferon gamma (IFN-γ > 8.0 IU/mL) in Nil tubes of QFT-GIT;•3. The study attempted to implement a plasma exchange pretreatment method on 82 patient samples (pretreated group) to improve the standard QFT-GIT with ITRs due to high Nil concentrations (Nil > 8 IU/mL). Forty samples (untreated group) among the 82 were processed using standard QFT-GIT for comparison.•4. Significantly decreased IFN-γ levels in Nil tubes were found with the method of pretreated QFT-GIT compared with regular QFT-GIT (p < 0.01);•5. Plasma exchange QFT-GIT yields better results than untreated QFT-GIT in the processing of high Nil concentrations. The features of indeterminate results (ITRs) due to high interferon gamma (IFN-γ > 8.0 IU/mL) concentrations in Nil tubes of QuantiFERON-TB Gold in-Tube (QFT-GIT) have not been well studied. Therefore, this study aimed at investigating the features of ITRs and optimization alternatives for this method. We used the plasma exchange method to reduce the ITR rate due to high Nil concentrations (Nil > 8.0 IU/mL) between March 2020 and September 2021 at Xiangya Hospital of Central South University in China. One hundred and eleven out of 28,193 patient samples were considered ITRs due to Nil > 8.0 IU/mL. Of these 111, blood was re-sampled from 82 patients (pretreated group) who received the plasma exchange. Moreover, 40 out of 82 (blood volume ≥ 5 mL) received pretreated QFT-GIT and standard QFT-GIT (untreated group) simultaneously, while the remaining 42 received pretreated QFT-GIT only. The statistical difference between groups was evaluated. Cohen’s kappa coefficient was used to assess the level of agreement between the pretreated and untreated group. Of the 28,193 subjects, 1,083 (3.8%) had ITRs, and 111 (0.4%) had ITRs due to Nil > 8.0 IU/mL. The population studied had a mean age of 52.9 years, and 70.3% were men, which is a larger proportion than that in patients with ITR and the overall population. Significantly decreased IFN-γ levels in Nil tubes were detected using the pretreated QFT-GIT compared with standard QFT-GIT (p < 0.01). The determinate results rate in the pretreated group was significantly higher than that of the untreated group (80% (32/40) vs 57.5%, (23/40), p = 0.03). Further comparison revealed that the pretreated group was consistent with the untreated group in 17/20 (85%) positive tests, 3/3 (100%) negative tests, and 6/17 (35.3%) ITRs. The overall agreement rate was 26/40 (65%) among all 40 subjects, and the κ value was 0.39 (minimal agreement). The majority of results obtained after pretreatment were positive (71.2%, 59/82) and the agreement rate between clinical diagnosis and pretreated QFT-GIT was at least 61.0% (39/59). Plasma exchange pretreated QFT-GIT yields more reliable results than untreated QFT-GIT when processing high Nil concentrations.